2001
DOI: 10.1046/j.1365-2648.2001.01775.x
|View full text |Cite
|
Sign up to set email alerts
|

Axillary and tympanic membrane temperature recording in the preterm neonate: a comparative study

Abstract: Whilst the findings cannot be applied to sick preterm neonate, it was concluded that tympanic membrane temperature recordings in healthy preterm neonates are safe, accurate, easy, and comfortable for the baby, and appropriate with this client group provided staff are trained in the technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 17 publications
0
30
1
Order By: Relevance
“…Preterm infants are prone to temperature maintenance problems due to immature thermoregulatory mechanism and relatively large body surface area. Therefore, body temperatures of preterm babies need to be measured regularly 1 . Minimal handling is a basic principle of neonatal care as frequent disturbance may lead to hypoxia and deterioration in their clinical condition.…”
Section: Introductionmentioning
confidence: 99%
“…Preterm infants are prone to temperature maintenance problems due to immature thermoregulatory mechanism and relatively large body surface area. Therefore, body temperatures of preterm babies need to be measured regularly 1 . Minimal handling is a basic principle of neonatal care as frequent disturbance may lead to hypoxia and deterioration in their clinical condition.…”
Section: Introductionmentioning
confidence: 99%
“…The Bland-Altman method was used (95% 'limits of agreement' mean 8 2 SD) to determine the level of agreement between axillary and rectal measurements [8,9] . The data were analyzed using SPSS version 11.0 (SPSS, Chicago, Ill., USA).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In many newborn nurseries rectal temperature measurements are common practice. The rectal route is a very practical method to determine the core temperature and is considered as 'gold standard' by many pediatricians [8][9][10] , some circumstances, e.g., anal atresia or necrotizing enterocolitis, excepted. Potential complications of rectal thermometry include spread of infection [11][12][13] and rectal perforation [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that temperature out of the normal range is closely related to the survival of infants. [6,7,10,11] Many decisions concerning the investigation and treatment of children may based on the results of temperature measurement alone. [12,13] As the basic sciences develop, temperature measurement methods and devices were improved.…”
Section: Introductionmentioning
confidence: 99%